Evaluation of the Quality of Online Passport Services (M-Paspor) in Improving Public Satisfaction at the Class I TPI Padang Immigration Office - Shania Dwi Brilliani; Rahmadhona Fitri Helmi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The implementation of the M-Passport application is a digital-based public service innovation aimed at improving the quality of passport services and public satisfaction. However, its implementation still faces several obstacles, such as system disruptions, limited service quotas, and low digital literacy among some residents. This study aims to evaluate the quality of online passport services (M-Passport) in improving public satisfaction at the Class I Immigration Office (TPI) in Padang. The study used a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model. The service evaluation refers to William N. Dunn's six indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results indicate that the M-Passport service has been running well and has facilitated the passport application process. Officers were deemed responsive, friendly, and communicative in serving the public. However, improvements are still needed to improve the stability of the application system, service capacity, and socialization of M-Passport use to continuously improve service quality and public satisfaction.